DEPENSAKA conservation of prime agricultural lands from urban sprawl using future land use planning and simulation within the City of San Jose Del Monte, Bulacan - Espina, Lance Ciple T. (College of Architecture, University of the Philippines Diliman, 2025)
Faced with urban sprawl and its associated challenges, such as the loss of agricultural lands, massive land conversions, and diverting from proper urban planning, how can the City of San Jose Del Monte, Bulacan, conserve its prime agricultural lands from the effects of urban sprawl such as urban encroachment and land conversion using future land use planning and simulation? The PLUS Model is designed as a transdisciplinary model that combines knowledge discovery, policy-making, and simulation to address the land use changes through various stages employing different methods. The model generates three future land use scenarios – Defensive, Protective, and Opportunistic. Using AHP, the scenario chosen is opportunistic to generate the landscape plan, aided by community preferences and researcher input. While it is inevitable that there will be loss of prime agricultural lands in future land use scenarios, choosing the opportunistic scenario to be applied for the future provides the least amount of change in terms of cropland, rangeland, and tree land cover loss while still achieving the goals of the CLUP, and providing for more socioeconomic opportunities for the city, hence protecting and enhancing the agricultural lands.